Determinan Profitabilitas Bank Pembiayaan Rakyat Syariah di Indonesia - Widiya Ningsih; Tenny Badina; Rita Rosiana (Akuntabilitas, 2016)
The purpose of this study is to analyze the influence of capital, asset quality, profitability and liquidity to profitabilitas. Populasi this study is the Islamic Rural Bank (BPRS) registered at Bank Indonesia. Total sample of 12 selected by using purposive sampling, uses secondary data obtained through the website www. bi. go. id. The analytical method used in this research is Multiple Linear Regression and Software SPSS 22 as a tool to test the hypothesis. The results of this study are: capital, asset quality and liquidity does not affect the profitability, earnings negatively affect profitability.